Multiple-Image Hiding Based on Cascaded Free-Space Wave Propagation Using the Structured Phase Mask for Lensless Optical Security System - Liansheng Sui; Xiao Zhang; Ailing Tian (IEEE Photonics Journal)
A novel optical multiple-image hiding method is proposed based on two cascaded free-space propagation transforms in this paper. With the use of the structured phase mask in the phase retrieval algorithm, a plain image is encoded to only one statistically independent phase-only mask. All retrieved phase masks are integrated into the noise-like ciphertext by using the phase mask multiplexing technique. When reconstructing an original plain image, the architecture of double random phase encoding system is directly adopted, where the structured phase mask and the corresponding decryption key mask are located at determined positions along the axis of propagation. Besides the propagation distances, the optical parameters such as wavelength, focal length, and topological charge of the structured mask are considered as the security keys to expand the key space. To the best of our knowledge, it is the first report on employing the structured phase mask in the process of phase retrieval algorithm, which can enhance the level of security greatly. Simulation results have been given to verify the feasibility and robustness of the proposed scheme.